Maintaining HIV testing and treatment services in Zambia during COVID-19: a story of success and resilience - Tina Chisenga; Menard Chihana; Paul Chishimba; Lastone Chitembo; Lloyd Mulenga; Andrew Silumesii; David Maman; Cheryl Johnson (Taylor & Francis Group, 2023)
Background Coronavirus disease 2019 (COVID-19) is caused by a virus called severe acute respiratory syndrome coronavirus. As countries struggled to control the spread of the virus through among other measures closure of health facilities, repurposing of health care workers, and restrictions on people's movement, HIV service delivery was affected. Objectives To assess the impact of COVID-19 on HIV service delivery in Zambia by comparing uptake of HIV services before and during COVID-19. Methods We used repeated cross-sectional quarterly and monthly data on HIV testing, HIV positivity rate, people living with HIV initiating ART and use of essential hospital services from July 2018 to December 2020. We assessed quarterly trends and measured proportionate changes comparing periods before and during COVID-19 divided into three different comparison time frames: (1) annual comparison 2019 versus 2020; (2) April to December 2019 versus same period in 2020; and (3) Quarter 1 of 2020 as base period versus each of the other quarters of year 2020. Results Annual HIV testing dropped by 43.7% (95%CI 43.6-43.7) in 2020 compared to 2019 and was similar by sex. Overall, annual recorded number of newly diagnosed PLHIV fell by 26.5% (95% CI 26.37-26.73) in 2020 compared to 2019, but HIV positivity rate was higher in 2020, 6.44% (95%CI 6.41-6.47) compared to 4.94% (95% CI 4.92-4.96) in 2019. Annual ART initiation dropped by 19.9% (95%CI 19.7-20.0) in 2020 compared to 2019 while use of essential hospital services dropped during the early months of COVID-19 April to August 2020 but picked up later in the year. Conclusion While COVID-19 had a negative impact on health service delivery, its impact on HIV service delivery was not huge. HIV policies that were implemented before COVID-19 on testing made it easier to adopt COVID-19 control measures and to continue providing HIV testing services without much disruption.